Influence of coffee blends and roasting process on the antioxidant activity of coffee - Odžaković, Božana; Džinić, Natalija; Kukrić, Zoran; Grujić, Slavica (Journal of Engineering & Processing Management, 2019)
The aim of this paper is to develop specification for the production of roasted coffee with improved nutritional quality. In this sense, the influence of different coffee blends and temperatures of roasting on the antioxidant activity of coffee was examined. Also, the composition of some bioactive components in the analyzed samples was determined. Two Arabica coffees of different quality and Robusta coffee were used for preparation of coffee blends. Experimentally determined green coffee blends B1, B2 and B3 were roasted at 167°C, 171°C and 175°C for 25 minutes in order to establish the effect of temperature roasting on the antioxidant activity and the content of bioactive components in blends. Based on results of DPPH and ABTS test, coffee blends B3 and B2, roasted at 171°C, had the highest (P<0.05) antioxidant activity. Those coffee blends had higher content of Robusta coffee than coffee blend B1. Results of this research can provide opportunities for development roasted ground coffee with improved nutritive quality, which could ensure competitiveness of producers in the target market.